Antimicrobial assay of trimethoxy carbonyl thiourea complexes - Umme Najehah, Ahmad (Universiti Malaysia Sarawak, UNIMAS, 2013)
Thiourea complexes had been proven to have the antimicrobial activity against specific bacteria and fungi. Seven series of different thiourea complexes compound were newly synthesized by the Department of Chemistry, UNIMAS and being tested in order to determine its antimicrobial activity on six different bacteria from Gram positive (Staphylococcus aureus, Listeria monocytogenes, and Bacillus cereus) and Gram negative bacteria (Escherichia coli, Enterobacter aerogenes, and Salmonella entriditis) and three species of fungi (Aspergillus flavus, Aspergillus niger, and Trichomonas vaginalis). The antimicrobial assay for bacteria was determined by using the Disc Diffusion technique and Antifungal testing for the antifungal assay. From the experiment, it was found that all the thiourea series had shown the resistance ability towards the tested bacteria, from good to moderate antibacterial activity while for the antifungal assay, all series showed resistance towards Aspergillus flavus and Aspergillus niger but no towards Tricoderma viride. This indicated that all thiourea complexes does not exhibit good antifungal ability towards Trichoderma viridae compare to the other test fungi.